Optimal Incentive Contracts under Moral Hazard When the Agent is Free to Leave - Andreas Roider; Florian Englmaier; Gerd Mühlheusser (Verein für Socialpolitik, 2010)
We investigate a moral hazard model with a one-sided commitment problem. That is, after effort provision, the agent is free to either stay with the principal or to leave and pursue his (ex-post) outside option, the value of which is increasing in effort. Depending on parameters, optimal contracts have interesting properties, such as first-best effort incentives, nonresponsiveness to underlying parameters, or inefficient separation. Moreover, the agent might suffer from a ceteris paribus improvement of his outside option. Potential applications of this framework include employment relationships and venture capital financing.
Keywords: D82; K31; M52; 330; moral hazard; limited commitment; ex-post outside option; limited liability